Secure Authentication Framework for SDN-IoT network using Keccak-256 and Bliss-B algorithms - Sahana, D. S.; Brahmananda, S. H. (International journal of information technology (Singapore. Online), 2023)
The software defined network (SDN) integrated with internet of things (IoT) reduces the scalability of IoT devices by managing the network. The SDN, on the other hand, is particularly subject to attacks since it relies on a centralised controller for network management, which attackers can simply alter. Communication between users and resources must be authenticated using the internal security approach. The proposed work introduces the SAF-Secure Authentication framework, which improves security and delivers efficient services to entities by efficiently utilising the existing challenges. Initially, all the users and applications are registered with attributes by using the keccak-256 hashing algorithm based on the registration, the Authentication is performed to ensure legitimacy by generating digital certificates based on the attributes by using Bliss-B algorithm. The comparison of the proposed method with several relevant works are performed to evaluate and validate the performance. The proposed SAF architecture provides better computation overhead and resource utilization.